The Odyssey of Women Writers in Antiquity: an example of coeducation and fostering vocational science - Rosario Moreno Soldevila; Manuel Alejandro González Muñoz; Alberto Marina Castillo; Marta Cuevas Caballero (The Journal of Classics Teaching)
This paper describes four methodological proposals for rescuing from oblivion and highlighting women writers in Graeco-Roman Antiquity. In workshops employing a variety of active methodologies, students become acquainted with Greek writers like Sappho, Diotima of Mantinea and Aspasia, and their Roman counterparts, including Sulpicia and Agrippina the Younger, while also becoming aware of the authorship of these women writers and their lack of visibility. The proposals take the shape of activities aimed at fostering a vocation for science among baccalaureate students in Spain but can also be easily adapted to secondary and even higher education in other educational contexts.